Shadow theater - Robson, Denny; Bailey, Vanessa (New York : Gloucester Press, 1991)
A step-by-step approach to shadow theater, from hand shadows to shadows with accessories made from simple materials.
Kirkus Review.
5.3
3-6
Keywords: Shadow shows -- Juvenile literature; Shadow puppets -- Juvenile literature; Puppet making -- Juvenile literature; Shadow shows; Shadow puppets; Puppets; Puppet making; Shadow pictures; Puppets and puppet plays; Puppet making; Shadow shows; Shadow puppets; Puppet making